An Examination of the Potential Costs of Universal Health Insurance in Ireland - Wren, Maev-Ann; Connolly, Sheelah; Nathan, Cunningham (ESRI, 2015)
This report examines the cost implications of the introduction of Universal Health Insurance (UHI) in Ireland, as proposed in the 2014 Government White Paper: The Path to Universal Healthcare: White Paper on Universal Health Insurance. The report presents the findings from in-depth modelling of the cost and financing implications of the introduction of this model of UHI in Ireland.